2019
DOI: 10.5194/hess-23-239-2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of flood restoration on surface–subsurface interactions in Rohrschollen Island (Upper Rhine river – France) using integrated hydrological modeling and thermal infrared imaging

Abstract: Abstract. Rohrschollen Island is an artificial island of the large Upper Rhine river whose geometry and hydrological dynamics are the result of engineering works during the 19th and 20th centuries. Before its channelization, the Rhine river was characterized by an intense hydromorphological activity which maintained a high level of biodiversity along the fluvial corridor. This functionality considerably decreased during the two last centuries. In 2012, a restoration project was launched to reactivate typical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A full description of the model and of the numerical techniques is available in Jeannot et al (2018). Various comparisons and bench tests (Weill et al, 2017;Jeannot et al, 2018) showed that simplifications brought by NIHM in the flow processes did not jeopardize accurate applications to complex hydrosystems (Jeannot et al, 2019).…”
Section: Hydrological Model 31 the Normally Integrated Hydrologicalmentioning
confidence: 99%
“…A full description of the model and of the numerical techniques is available in Jeannot et al (2018). Various comparisons and bench tests (Weill et al, 2017;Jeannot et al, 2018) showed that simplifications brought by NIHM in the flow processes did not jeopardize accurate applications to complex hydrosystems (Jeannot et al, 2019).…”
Section: Hydrological Model 31 the Normally Integrated Hydrologicalmentioning
confidence: 99%
“…The model NIHM used to simulate the response of the Strengbach catchment is a physically based spatially distributed model that describes and couples the flow processes occurring in the surface and subsurface compartments of a watershed [36][37][38][39]. The model can describe flow in the subsurface, in a 1-D stream network, and also over the 2-D land surface.…”
Section: The Normally Integrated Hydrological Model (Nihm)mentioning
confidence: 99%
“…This technique drastically reduces the meshing effort and the computational cost while preserving the physics, especially for systems with contrastive topography, as is the case with the Strengbach catchment discussed here. Conversely, the technique also works for flat systems needing a refined mesh to capture small topographic depressions, as exemplified by a riverine island [38,39]. The description of flow in the 1-D stream network is based on a 1-D formulation of the diffusive wave approximation of the St-Venant equations.…”
Section: The Normally Integrated Hydrological Model (Nihm)mentioning
confidence: 99%
See 2 more Smart Citations